Estimating demand for quadruple-play tariffs: The impact on consumer surplus - Lukasz Grzybowski; Julienne Liang (International Telecommunications Society (ITS), 2014)
This paper estimates demand for quadruple play mobile tariffs using a database of subscribers to a single mobile operator from a single town in a European country which has full coverage with both ADSL and FTTH broadband technologies. Based on the demand estimation we find that consumer valuation of FTTH broadband in 2013 increased over time while ADSL lost on attractiveness relative to FTTH but also in absolute terms, which suggests that consumers increasingly care about the speed of connection offered by FTTH. The consumer surplus increased substantially due to the introduction of quadruple play tariffs, and especially with the introduction of FTTH, and ongoing transition of consumers from less valued quadruple play tariffs with ADSL to more valued with FTTH. We also find that for quadruple play subscribers mobile data is complementary to fixed broadband access, which suggests that these consumers use Internet access via mobile handsets to sample online content but they complete their online activity using fixed Internet access at home. On the other hand, mobile voice usage is a substitute to fixed broadband access and consumers reduce their voice consumption once they get broadband connection. We also find that there are substantial switching costs between tariffs, which other things being equal greatly decrease consumer surplus.
Keywords: L13; L43; L96; 330; Quadruple play; FTTH; ADSL; Mobile data; Switching costs